Analysis of red chilli drying kinetics affected by low-temperature long time blanching. Issue 3 (July 2021) - Lestari, N; Samsuar,
Abstract: The drying kinetics of red chillies in the effect of low-temperature long time blanching were investigated. The blanching process was carried out at 70 °C for 10, 15, and 20 minutes. The drying process lasts for 32 to 35 hours to reduce the moisture content from 82.24% (wb) to 8.84% (wb). The experimental data were fitted to three mathematical models of thin-layer drying, namely the Henderson and Pabis, Lewis, and Page models. The result shows that the Page model is the most suitable model for predicting moisture ratio in chilli drying with low-temperature long time blanching treatment. This suitability is evidenced by the highest R 2 value, which ranges from 0.9709 to 0.9786, and also the lowest RMSE and MBE values range from 0.0503 to 0.0579 and 0.0025 to 0.0034, respectively. Meanwhile, the effective moisture diffusivity varies from 5.6300 × 10 −9 m 2 /s to 6.5662 × 10 −9 m 2 /s for the treatments studied.